The Correlational Relationship between Morphological Awareness and Vocabulary Knowledge of Saudi EFL Learners: Evidence from King Khalid University - Fadi Al-Khasawneh; Ibrahim Huwari (University of Muhammadiyah Prof. DR. HAMKA, 2020)
Vocabulary size knowledge is considered as a crucial factor in academic success and it could be enlarged through several ways. The purpose of the present study was to examine the correlation between morphological awareness and vocabulary size knowledge of Saudi participants at King Khalid University. The present study used the correlational research design, which investigates the relationship or correlation between variables. The participants of this study included 67 male students from two sections of Phonology course taught by the researcher. Two research instruments were used to gather the data of this study, Nation’s (1990) Vocabulary Level Test and the Morphological Awareness Test adopted from Alsalamah (2011) which was originally developed by Chang, Wagner, Muse, & Chow (2005). The SPSS software (version 18) was used to analyze the data of present study. The results of the study revealed that the students’ vocabulary size was within 4.000 words level and 5.000 words level (4686 word families). The results have also showed relatively low performance in the Morphological Awareness Test (i.e. Morphological Structure Test and Morpheme Identification Test). Concerning the correlation between the two variables, the results showed no significant correlation between morphological awareness and vocabulary size.